Archetypal, identical, similar? Seamus Heaney's "Punishment" revisited - Montezanti, Miguel Angel (2008)
"Punishment" by Seamus Heaney reflects upon the relationship between a prehistoric girl killed in a ritual and two modern Irish girls punished as a consequence of political strife. My point is that Heaney's poem cannot be taken as a one-sided approach to identity, to stereotypes or archetypes. The introduction of a Christian hypotext works in such a way that no element in any of the sequences can be taken as a univocal "archetype" of the other two. Notions such as "archetype", "repetition" and "rite" are critically discussed. The poet interrogates the painful reality of Irish contemporary events and his own reactions, rather than acquiescing to a conclusive pattern of revenge.